Sweden : Selected Issues. (IMF Staff Country Reports; Country Report, 1999)
This Selected Issues paper describes a variety of methodologies for estimating a country's potential output level and presents empirical estimates for Sweden. The paper explains why these methods produce a variety of results, some of which are more plausible than others. The paper looks more closely at one aspect of growth in potential output: how it has been affected by the structural policy improvements of the past several years. The paper examines the pattern of output and unemployment over time to separate permanent changes from cyclical and other temporary changes.